Pertimbangan Khusus Pemberian Nutrisi Enteral pada Pasien ICU Non-ARDS dengan Posisi Prone Jangka Panjang - Cahyo Purnomo, Ika; Jufan, Ahmad Yun (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2024)
Background: Early enteral nutrition (EN) is recommended in critical care to reduce the complications. However, hesitancy exists when administering EN in a prone position. We report a case of non-ARDS patient with extended periods of prone position receiving EN. Case: A 18 years, quadriplegic, male, underwent cervical internal fixation and gluteal flap. Postoperatively, he was to be prone positioned for 10 days. Analgesics was tramadol and NSAID. NGT placement and patency was confirmed. The bed was tilted 30º upright and EN intermittently administered every 4 h, followed by GRV check in 2 h. Intake was gradually increased in each feeding. Patient was discharged after 48 h. Further management was also in the prone position. Discussions: Feeding tolerance reduction and tube displacement is associated with EN in prone patients. Pre-feeding tube patency and position check is imperative. Feeding tolerance, GRV, and vomiting should be monitored. No recommendation for ultrasound monitoring. Upright tilting was to aid nutrition passage by gravity. Prokinetics and pump feeding were not performed in this patient. Tolerance was excellent, no complications in nutritional management were found. Conclusions: EN during a prone position is challenging, yet the findings support that EN is feasible and can be well tolerated.